2021
DOI: 10.1002/anie.202015622
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Novel van der Waals Boron Oxides with Superior Deep‐Ultraviolet Nonlinear Optical Performance

Abstract: Deep‐ultraviolet nonlinear optical (DUV NLO) materials are attracting increasing attention because of their structural diversity and complexity. Using the two‐dimensional (2D) crystal structure prediction method combined with the first‐principles calculations, here we propose layered 18‐membered‐ring (18MR) boron oxide B2O3 polymorphs as high‐performance NLO materials. 18MR‐B2O3 with the AA and AB stackings are potential DUV NLO materials. The superior performing 18MR‐B2O3AB has an unprecedentedly high second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Furthermore, another design strategy to eliminate the A-site cations, i.e., via van der Waals (vdW) connection, has been proposed, and a series of possible DUV NLO structures have been accordingly predicted 68 , 73 , 75 , 78 , 81 . Among them, an existing berborite (Be 2 BO 5 H 3 , BBH) mineral as shown in Fig.…”
Section: First-principles Exploration Of New Duv Nlo Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, another design strategy to eliminate the A-site cations, i.e., via van der Waals (vdW) connection, has been proposed, and a series of possible DUV NLO structures have been accordingly predicted 68 , 73 , 75 , 78 , 81 . Among them, an existing berborite (Be 2 BO 5 H 3 , BBH) mineral as shown in Fig.…”
Section: First-principles Exploration Of New Duv Nlo Crystalsmentioning
confidence: 99%
“…To address this challenge, over the past decade several design strategies have been proposed to promote the performance improvement of DUV NLO crystals 66 – 69 . By combining advanced first-principles modeling and simulations, a series of potential DUV PM SHG crystals were evaluated, designed, and predicted 69 75 , some of which have been partially verified experimentally 50 , 76 .…”
Section: First-principles Exploration Of New Duv Nlo Crystalsmentioning
confidence: 99%
“…First-principles studies demonstrated that it might indeed exhibit potential DUV NLO performance. [14] Depending on our DUV NLO materials design blueprint, we proposed two basic design principles: [15] (I) to realize large E g and SHG, the selected NLO-active structural motifs should include polar anionic units with sufficiently large energy differences of cation-anion atomic orbitals, for example, triangular sp 2 -hybird (BO 3 ) 3À and (CO 3 ) 2À , tetrahedral sp 3 -hybird (BO 4 ) 5À and (SO 4 ) 2À , etc., aligned in a manner to exhibit significant SH polarization; and (II) to realize stable vdW layered structures, the anionic motifs should form a planar or quasi-planar framework by sharing their corner anions; meanwhile, there should be no unpaired electrons on the outmost surface, avoiding to form covalent bonds between neighboring layers. Based on the principles, we have schematically illustrated our design proposal in Figure 1 and summarized four potentially feasible designs derived from KBBF for the vdW versions:…”
Section: D Vdw Duv Nlo Materialsmentioning
confidence: 99%
“…6–9 In general, the B atoms can be sp 2 or sp 3 hybridized with the O atoms to constitute [BO 3 ] and [BO 4 ] groups, which can form a variety of FBBs through common vertex or common edge connections. 10–17 For example, typical FBBs include [B 2 O 5 ] units in Li 2 Na 2 B 2 O 5 , 18 [B 3 O 6 ] units in β-BaB 2 O 4 (BBO), 19 [B 3 O 7 ] units in LiB 3 O 5 , 20 CsB 3 O 5 , 21 [B 4 O 8 ] units in Li 6 B 4 O 9 , 22 and [B 7 O 16 ] units in Na 3 B 7 O 12 23 etc . The variety of the linkage modes of these FBBs leads to the flexible structure of borates which exhibit zero-dimensional (0D) isolated clusters, 1D chains, 2D layers, and 3D frameworks.…”
Section: Introductionmentioning
confidence: 99%